Development of captive broodstock of t he grey mullet, Mugil cephalus (L) - Abraham, Mathew; Kailasam, M; Chandra, P Kishore; Siharanee, P; Rajendran, K V; Charles, A V K (Indian Journal of Fisheries, 2011)
A captive broodstock of the grey mullet Mugil cephalus has been successfullydeveloped at Muttukadu experimental station of the Central Institute ofBrackishwater Aquaculture. A stock of 72 sub-adult and adult fish in the sizerange of 290-450 mm/300-1,200 g procured from the commercial catches weremaintained in 100 tonne capacity RCC tanks from January '96. During 1996, about20% of the stock, both males and females attained final maturity. In 1997, about60% of the females and 80% of the males attained final maturity. In mature femalesova diameter of the matured oocytes ranged from 525 to 614 urn and the maturemales were in oozing stage.